In Vitro Assessment of the Antibacterial Activity of Sapindus rarak (Lerak) and Its Influence on Cellular Immune Markers During Escherichia coli Infection - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Biology, Medicine, & Natural Product Chemistry, 2026)
Antibiotic-resistant Escherichia coli remains a major public health concern, prompting interest in plant-derived compounds with both antimicrobial and immunomodulatory functions. This study evaluated the antibacterial activity of Sapindus rarak (lerak) extract and its influence on macrophage cytokine responses during E. coli stimulation. Lerak pericarp extract was prepared using 70% ethanol and tested against E. coli ATCC 25922 using broth microdilution. Immunomodulatory effects were assessed in RAW 264.7 macrophages exposed to heat-killed E. coli, followed by treatment with sub-MIC concentrations of the extract. The results showed moderate antibacterial activity, with a minimum inhibitory concentration of 250 microgram/mL and a minimum bactericidal concentration of 500 microgram/mL. Cell viability exceeded 90% at 50–100 microgram/mL, confirming suitability for immunological assays. Lerak significantly reduced TNF-alpha and IL-6 production while increasing IL-10 levels, indicating suppression of excessive inflammation and enhancement of regulatory responses. These findings suggest that S. rarak possesses dual antibacterial and immunomodulatory properties, highlighting its potential as a complementary therapeutic candidate for managing E. coli infections where inflammation contributes to disease severity.